Observations of Arctic snow and sea ice cover from CALIOP lidar measurements - Lu, Xiaomei; Hu, Yongxiang; Liu, Zhaoyan; Rodier, Sharon; Vaughan, Mark; Lucker, Patricia; Trepte, Charles; Pelon, Jacques (Remote Sensing of Environment, 2017)
International audience This paper describes the development and validation of a method to accurately identify snow/ice cover, surface melting, land surface and open water in polar regions using polar-orbiting Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) lidar measurements from the Cloud and Aerosol Lidar and Infrared Pathfinder Observation (CALIPSO) mission. The technique is based on the relationship between integrated attenuated backscatter color ratio and integrated depolarization ratio, and is proven to efficiently separate snow/ice cover and surface melting from open water and land surfaces. The method has been applied to 10 years (2006–2016) of CALIOP data to study the seasonal and inter-annual variability of Arctic sea ice cover and its declining trend. Results show that the area fraction of snow cover over land at latitudes > 60°N varied between 0.9 during winter and 0.1 in summer. The CALIOP observations of Arctic sea ice cover exhibit a strong seasonal cycle and significant inter-annual variability, which are consistent with the passive microwave-based sea ice results. The > 10 years of CALIOP continuous observations of the snow/ice cover will benefit the communities modeling snow/ice melting and climate change.